Identification and Map-Based Cloning of the Light-Induced Lesion Mimic Mutant 1 (LIL1) Gene in Rice - Zhou, Qian; Zhang, Zhifei; Liu, Tiantian; Gao, Bida; Xiong, Xingyao (Frontiers in Plant Science, 2017)
The hypersensitive response (HR) is a mechanism by which plants prevent the spread of pathogen. Despite extensive study, the molecular mechanisms underlying HR remain poorly understood. Lesion mimic mutants (LMMs), such as LIL1 that was identified in an ethylmethane sulfonate mutagenized population of Indica rice (Oryza sativa L. ssp. Indica) 93-11, can be used to study the HR. Under natural field conditions, the leaves of LIL1 mutant plants exhibited light-induced, small, rust-red lesions that first appeared at the leaf tips and subsequently expanded throughout the entire leaf blade to the leaf sheath. Histochemical staining indicated that LIL1 lesions displayed an abnormal accumulation of reactive oxygen species (ROS) and resulted from programmed cell death (PCD). The LIL1 mutants also displayed increased expression of defence-related genes and enhanced resistance to rice blast fungus (Magnaporthe grisea). Genetic analysis showed that mutation of LIL1 created a semi-dominant allele. Using 1,758 individuals in the F2 population, LIL1 was mapped in a 222.3 kb region on the long arm of chromosome 7. That contains 12 predicted open reading frames (ORFs). Sequence analysis of these 12 candidate genes revealed a G to A base substitution in the fourth exon of LOC_Os07g30510, a putative cysteine-rich receptor-like kinase (CRK), which led to an amino acid change (Val 429 to Ile) in the LIL1 protein. Comparison of the transcript accumulation of the 12 candidate genes between LIL1 and 93-11 revealed that LOC_Os07g30510 was up-regulated significantly in LIL1. Overexpression of the LOC_Os07g30510 gene from LIL1 induced a LIL1-like lesion phenotype in Nipponbare. Thus, LIL1 is a novel LMM in rice that will facilitate the further study of the molecular mechanisms of HR and the rice blast resistance.